2016
DOI: 10.1097/mib.0000000000000875
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Diversity Is Reduced in Smokers with Crohnʼs Disease

Abstract: Article first published online 10 August 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 56 publications
5
63
0
2
Order By: Relevance
“…Thus, studies targeting selected bacterial groups reported that patients with active CD, who also smoked, had microbial profiles different from those of non-smoking patients with CD. Similar results were found in healthy smoking controls, suggesting that the association related not to intestinal inflammation but, instead, to a direct impacts of smoking on the microbiota [129,130]. Differences between mice and humans at the level of the gut microbiota limit the usefulness of mouse models, relevant to CS, gut microbiota and IBD.…”
Section: Gut Microbiotasupporting
confidence: 70%
“…Thus, studies targeting selected bacterial groups reported that patients with active CD, who also smoked, had microbial profiles different from those of non-smoking patients with CD. Similar results were found in healthy smoking controls, suggesting that the association related not to intestinal inflammation but, instead, to a direct impacts of smoking on the microbiota [129,130]. Differences between mice and humans at the level of the gut microbiota limit the usefulness of mouse models, relevant to CS, gut microbiota and IBD.…”
Section: Gut Microbiotasupporting
confidence: 70%
“…Enterorhabdus and Pedobacter were also decreased in PS group of rats. Enterorhabdus was shown to be associated with autism spectrum disorder in a murine model (de Theije et al, 2014) and with a genetic variant of the human leukocyte antigen complex that has been related to inflammatory diseases (Opstelten et al, 2016). Pedobacter, heparinase-produsing bacteria, are a normal component of the gut microbiota of healthy fish (Wang et al, 2018a) and the medicinal leech (Ott et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with non-smoking Crohn's disease patients, gut microbial gene richness, genus and species diversity were reduced in smoking patients, with lower relative abundance of the genera Collinsella, Enterorhabdus and Gordonibacter, and of Faecalibacterium prausnitzii. 147 Moreover, significant alterations in microbiota composition has been reported in healthy smokers, which reverses upon smoking cessation, with marked increases in overall microbial diversity and an increase in the phyla Firmicutes and Actinobacteria, as well as a lower proportion of Bacteroidetes and Proteobacteria, compared with continuing smokers and non-smokers. 148 Colonic bacterial dysbiosis was also reported in mice chronically (24 weeks) exposed to cigarette smoke, with increases in Lachnospiraceae sp.…”
Section: The Role Of the Microbiome In Copdmentioning
confidence: 99%